SUSTAINABILITY OF RESEARCH CENTRES IN RELATION TO GENERAL AND ACTUAL RISKS - Hadzima, Branislav; Sedivy, Stefan; Pepucha, Lubomír; Zuziaková, Ingrid (European Scientific Journal, ESJ, 2015)
Direct application of University Science Parks and Research Centres operational models for the needs of sustainability of their research and development activities in the period after completion of their financial support from structural funds (e.g. after 2015) represents one of the important issues for their direct leader employees. The definition and ways of implementing said models cause enormous discussions already nowadays in science and research environment. Time lead of such discussion shows that the issue is not really solved and represents a serious risk for projects´ sustainability, which is so vital not just in the decisive monitored period of 5 years after the project completion, but mainly in mid-term and long-term horizon. It is necessary to connect sustainability assurance with an active approach within the frame of the assembly regulation process of both the actual and predictor risk by following the most important goal - the competitiveness within European research area and all-society contribution of its actual activities.